Digitalization Capabilities as Enablers of Value Co‐Creation in Servitizing Firms. Issue 1 (January 2017) - Lenka, Sambit; Parida, Vinit; Wincent, Joakim
ABSTRACT: As manufacturing companies pursue a servitization strategy, they are increasingly relying on developing digitalization capabilities to interact and co‐create value with their customers. However, many lack an understanding of what constitutes digitalization capabilities and how they can create value with customers. To address these questions, the study builds on qualitative data from four industrial manufacturing firms to conceptualize three underlying subcomponents of digitalization capabilities, namely, intelligence capability, connect capability, and analytic capability. The study identifies and explains how digitalization capabilities enable value co‐creation with customers through perceptive and responsive mechanisms. This study contributes to the servitization literature by showcasing how digitalization capabilities are enabling value co‐creation in a business‐to‐business context.